The Trotula : an English translation of the medieval compendium of women's medicine - Green, Monica Helen; Green, Monica Helen (University of Pennsylvania Press, 2002)
The Trotula was the most influential compendium on women's medicine in medieval Europe. Green here presents the first modern English translation of the so-called standardized Trotula ensemble, a composite form of the texts that was produced in the mid-thirteenth century and circulated widely in learned circles.
Keywords: Trotula -- De mulierum passionibus; Gynecology -- Early works to 1800.; Obstetrics -- Early works to 1800.; Women -- Health and hygiene -- Early works to 1800.; Medicine -- Italy -- Salerno -- History.; Medicine, Medieval.; History, Medieval; Gynécologie -- Ouvrages avant 1800.; Obstétrique -- Ouvrages avant 1800.; Médecine -- Italie -- Salerne -- Histoire.; Médecine médiévale.; LITERARY COLLECTIONS -- Ancient & Classical.; Gynecology; Medicine; Medicine, Medieval; Obstetrics; Women -- Health and hygiene; Italy -- Salerno; Vrouwen.; Gynaecologie.; Verloskunde.; Caregiving.; Gender Studies.; Health.; History.; Medicine.; Medieval and Renaissance Studies.; Women's Studies.; Early works; History